An uncommon history of common courtesy : how manners shaped the world - Patrick, Bethanne Kelly. (National Geographic ; Publishers Group UK [distributor], 2011)
With engaging and artfully presented text, including sidebars on media mavens throughout history, social gaffes, and archaic manners, this book is as entertaining as it is informative. Readers delve into cultural similarities and differences through lively passages, colorful photography, and sidebars on unique history.